Building Reliable Cloud Services Using P# (Experience Report) - Deligiannis, Pantazis; Ganapathy, Nar; Lal, Akash; Qadeer, Shaz (arXiv, 2020)
Cloud services must typically be distributed across a large number of machines in order to make use of multiple compute and storage resources. This opens the programmer to several sources of complexity such as concurrency, order of message delivery, lossy network, timeouts and failures, all of which impose a high cognitive burden. This paper presents evidence that technology inspired by formal-methods, delivered as part of a programming framework, can help address these challenges. In particular, we describe the experience of several engineering teams in Microsoft Azure that used the open-source P# programming framework to build multiple reliable cloud services. P# imposes a principled design pattern that allows writing formal specifications alongside production code that can be systematically tested, without deviating from routine engineering practices. Engineering teams that have been using P# have reported dramatically increased productivity (in time taken to push new features to production) as well as services that have been running live for months without any issues in features developed and tested with P#.